Take It off-site world order and international institutions after COVID-19 (2020)
COVID-19 changes everything, we are told. We know, almost certainly, that it does not. COVID-19 is an accelerator of global changes that were already under way, much more than it is a generator of sharp shifts in direction. The cumulative impact of these trends that preceded the pandemic was to begin the transition away from American hegemony toward a world order framed by the relationship between China and the United States. The pandemic will accelerate these processes of world order change. Whether that relationship will become one of all-out rivalry or collaborative competition will be determined by the policy choices leaders in both capitals make.